Writing, violence and disgust: a reading of "Mejor la ausencia" (2017) by Edurne Portela - Fernández Prieto, Celia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The novel Mejor la ausencia (2017) by Edurne Portela develops a storyline about domestic abuse in the social and political context of Euskadi, the Spanish Basque country, in the 1980s and 90s. It is recounted from the child and teenage voice and gaze of the narrator and protagonist, Amaia Gorostiaga. In this paper the novel’s complex enunciative and metaliterary structure is analysed, its writing equates to an act of driving out a memory that carries the physical and emotional scars of the violence, manifested through the language of disgust.